The vaccines-associated Arthus reaction - Baozhen Peng; Mingwei Wei; Feng-Cai Zhu; Jing-Xin Li (Taylor & Francis Group, 2019)
The Arthus reaction is a rare adverse reaction that usually occurs after vaccination with large and more severe local reactions, belonging to type Ⅲ hypersensitivity reaction. This reaction is characterized by pain, swelling, induration (Tissue that becomes firm) and edema, even accompanied by severe necrosis or ulceration at the injection sites. However, most of mild cases generally can be cured without treatment, and only severe cases need to be treated with anti-allergy. Therefore, this adverse reaction is often ignored by people. We searched PubMed, Web of Science and Chinese database (CNKI database and Wan Fang database) for published studies using the terms "Arthus reaction" or "Arthus phenomenon", combined with "vaccine", with no date or language restrictions for all publications before January 28, 2019. Only 30 cases of Arthus reaction were found, of which only one case died.4 cases of Arthus reaction post-dose-1 were reported in the review. The proportion of Arthus reaction occurred after the first, second and third injections in those case reports was 13.3%, 50.0%, and 23.3%, respectively. Arthus reaction was determined according to the clinical symptoms (The symptoms which were observed by the researchers, such as red, swelling and painful with itching at or around the injection sites). The specific causes of Arthus reaction after one dose of vaccination are not described in detail in literatures. Therefore, it could be hypothesized that the case has a pre-existing specific IgG (Such as pre-existing antibody, etc.) to cause the Arthus reaction. And 17 reported cases were observed in children younger than 6 y. In addition, we collected only 18 cases of bacterial vaccine-induced Arthus reaction and 12 cases of viral vaccines. However, there are no other data (Such as the total number and incidence rate of vaccination) in literatures, so we cannot compare statistically significant differences. At presents, no previous reviews of vaccine-induced Arthus reaction have been found. Thus, a systematic review about vaccine-associated Arthus reaction is urgently needed to deepen people's understanding and concern of this phenomenon. In this manuscript, we retrospectively reviewed the description of the discovery process and mechanisms of Arthus reaction, a description of the characteristics of Arthus reaction cases, reporting the Arthus reaction cases in China during 2010-2015, diagnostic criteria and general treatment, preventive measures of Arthus reaction, and challenges remaining to be investigated in the future.